Combining Tools to Design and Develop Software Support for Capabilities - Martin Henkel; Christina Stratigaki; Janis Stirna; Pericles Loucopoulos; Yannis Zorgios; Antonis Migiakis (Complex Systems Informatics and Modeling Quarterly)
Analyzing, designing and implementing software systems based on the concept of capabilities have several benefits, such as the ability to design efficient monitoring of capabilities and their execution context. Today, there exist new model-driven methods and development tools that support capability-based analysis, design, and implementation. However, there are also a plethora of existing efficient development tools that are currently in use by organizations. In this article, we examine how a new set of capability based tools, the Capability Driven Development (CDD) environment, can be combined with model-driven development tools to leverage both novel capability-based functionality and the proven functionality of existing tools. We base the examination on a case study where an existing model-driven tool is combined with the CDD environment.